PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 023 SEDINGINAN KECAMATAN TANAH PUTIH - Rusmidar '; Otang Kurniaman; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the low learning outcomes IPA Elementary School fifth grade students Sedinginan 023, as seen from the average value of students is 59.75. Of the 20 students who achieve above KKM only 8 people (40%), while that has not reached KKM 12 people (60%), KKM predetermined value is 70. The problem of this study "whether the application of the model Contexual Teaching and Learning ( CTL) can improve learning outcomes IPA at Elementary School fifth grade students 023 Sedinginan? The researchers' goal to improve science learning outcomes through the implementation of the model Contexual Teaching and Learning (CTL) in SD Negeri 023 Sedinginan. The experiment was conducted in the second semester (2) The school year 2014/2015 in March and April 2015. The subjects were students of class V Elementary School 023 Sedinginan the number of students 20 people, consisting of 13 women 7 men. Design research is classroom action research (PTK). This research was conducted in two cycles, ie four meetings by discussing the lessons and twice held the final repetition of the cycle. With the implementation of the application of the model (CTL) it can improve student learning outcomes IPA, seen from the percentage of completeness student learning outcomes in basic score is the average of 59.75 thus be increased to 40% and with an average of 67, and to 75% in I cycle, while on the second cycle increased again by an average of 78.75 to be 90%, as seen from the percentage of teachers increased activity in the first cycle is 67.2% in the second cycle increased to 85.9%. The percentage of student activity also increased in the first cycle 68.8% while the second cycle increased to 89%. From the above explanation can be concluded that the application of the model Contexual Teaching and Learning (CTL) can improve learning outcomes fifth grade science students of SD Negeri 023 Sedinginan.Keywords: Model Contexual Teaching and learning (CTL), the results of Students learn science